PENGARUH BEBAN KERJA DAN STRESS KERJA TERHADAP KINERJA PERAWAT RUMAH SAKIT CAHAYA MEDIKA - Dela Syeikholbi Desi; Dewi Puspaningtyas; Jumawan; Edward Efendi Silalahi (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2023)
The importance of the role of human resources is a determinant for the sustainability of the company's running. Nurse performance problems occur due to excessive workload and result in nurse work stress. This research was conducted at Cahaya Medika Hospital. In this study, the authors used a quantitative approach. The types of data used in this study are primary data and secondary data, with calculations using SPSS version 25. The population in the study was 63 nurses. The number of samples used corresponds to the number of the population. Based on the results of the analysis of workload variable research (X1), a calculated t value of 2.647 > 1.99962 (t table) was obtained with a sig of 0.010 < 0.05 or a sig value smaller than 0.05. This means that partially Workload (X1) has a positive and significant effect on Performance (Y). Variable Work Stress (X2), obtained a calculated t value of 3.925 > 1.99962 (t table) with a sig of 0.000 < 0.05 or a sig value smaller than 0.05. This means that partially Work Stress (X2) has a positive and significant effect on Performance (Y). Simultaneous tests are known if obtained F count of 35.454 > 3.148 (F table) with a sig value of 0.000 < 0.05 or a significant value of less than 0.05. Based on that, H1 and H2 are accepted which means that simultaneously Workload (X1) and Work Stress (X2) have a positive and significant effect on Performance (Y).